E-GOVERMENT BASED EDUCATION POLICY INNOVATION THROUGH E-PANRITA APPLICATIONS (ONLINE ATTENDANCE STUDY FOR TEACHER AT SMAN 3 LUWU) - Rahman, Miftahul; Mustari, Nuryanti; N, Novitasari; Atirah, Sitti (Government Studies of Muhammadiyah Malang University/AIPPTM, 2020)
Innovation and policy in the public sector are two terms that complement each other. Every policy, in principle, must in principle contain new innovations. This study aims to determine the innovation of E-Governmment-based educational policies through the application of E-Panrita on online attendance for teachers at SMAN 3 Luwu. This type of research is a qualitative research with descriptive research type with data collection techniques direct observation to the study site, in-depth interviews and documentation. The results showed that the innovation of the E-Panrita application is seen in the product, where in the E-Panrita application product there is a change in teacher absenteeism which previously teachers absent with a manual system is now now with an online system to facilitate the Disdik in monitoring teachers every day and the pre-existing facilities have met but still need improvement. Now the teachers can do the absence simply by using their mobile phones or gadgets. Furthermore, the method, in the form of a strategy in the innovation of E-Panrita policies such as socialization in each region. The supporting and inhibiting factors of E-Panrita application education policy innovation in online absenteeism for teachers at SMAN 3 Luwu are supporting factors including resources, regulations, teacher commitment and technology. Inhibiting factors include the network and individual understanding of the teacher.Keywords: Educational Policy, E-Government, E-Panrita